The long-term (24-month) effect on health and well-being of the Lifestyle Matters community-based intervention in people aged 65 years and over: a qualitative study - Chatters, Robin; Roberts, Jennifer; Mountain, Gail; Cook, Sarah; Windle, Gill; Craig, Claire; Sprange, Kirsty (BMJ Publishing Group Ltd, 2017)
Objectives